Morphometric study of foramen magnum in human dry skulls - Sulabha Hanumant Deshpande; Ashwini Balasaheb Nuchhi; Balappa Murigeppa Bannur; Babasaheb Gurusiddappagouda Patil (Wolters Kluwer Medknow Publications, 2017)
Background: Anthropologists are often faced with the task of assigning sex to remains that are incomplete, fragmented or damaged as may result from incidents such as mass disasters, airplane crashes, fire, explosions or physical violence. The size of foramen magnum does not change after puberty, not related to age then after. It is this part of the cranial base which can withstand fire explosions as the area is covered by large amount of soft tissue. Hence the foramen magnum was considered for studying the sexual differences in skull. Aims: To analyse the morphology and morphometry of foramen magnum, and the impact of these variables on sex determination of skull. Materials and Methods: 68 male and 68 female adult dry skulls were used for the study. The shapes of foramen magnum were studied. Results: In total, oval was the most common shape comprising of 61.76%, 16.17% arrow head, 11.76% irregular and 10.29% round. The sagittal diameter was 33.0[28-40] mm in males and 33.0[28-43] in females and transverse diameters of foramen magnum were 27[21-31] in males and 26.0[23-33]mm in females. Area of foramen magnum was calculated using Radinsky and Teixeria formulae and foramen magnum index was calculated. Mean, standard deviation and median [where ever required] were calculated. Student t test and Mann Whitney U test/ T test were applied. We did not find significant difference between male and female values. Conclusion: Our study did not demonstrate statistically significant difference in expression of sexual differences in the foramen magnum. However if detailed analysis is done with greater sample size by discriminant function analysis, it may prove useful in predicting sex in severely fragmented cranial bases.